Adrenal incidentaloma: cardiovascular and metabolic effects of mild cortisol excess - Kelsall, Alan (Gland Surg, 2020)
In the vast majority of cases adrenal incidentalomas (AI) are benign adrenocortical adenomas. They are present in up to 10% of the population over 70 years, with incidence increasing with age. Mild cortisol excess (MCE) in the context of AI is defined as autonomous cortisol secretion (ACS) in the absence of the classical clinical features of Cushing’s syndrome. MCE has been reported in up to at least one third of patients with AI. Numerous studies have shown that MCE in AI is associated with increased cardiovascular events and mortality, likely to be consequent upon both hemodynamic changes and inflammatory pathways, and a worse metabolic phenotype characterized by: pancreatic β-cell dysfunction, insulin resistance, visceral obesity and dyslipidemia. There is currently no level 3 evidence from large intervention randomized controlled trials to guide management of MCE in AI, and there is a lack of predictive tools to allow stratification to intervention of only those patients who would benefit in terms of improved metabolic and cardiovascular end-points. Here, we describe the mal-effects of cortisol on cardiovascular and metabolic tissues and discuss management strategies based on current largely observational data.